2015
DOI: 10.1097/bpo.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Need for Surgical Intervention in Patients With Idiopathic Clubfoot

Abstract: Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 25 publications
4
37
1
Order By: Relevance
“…The authors found that the Ponseti brace protocol is essential in order to decrease the rate of additional surgery. Goldstein et al [ 26 ] treated 86 patients (134 feet), with a minimum follow-up of 3 years. Forty-three out of 134 feet (32 %) underwent additional surgery other than tenotomy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that the Ponseti brace protocol is essential in order to decrease the rate of additional surgery. Goldstein et al [ 26 ] treated 86 patients (134 feet), with a minimum follow-up of 3 years. Forty-three out of 134 feet (32 %) underwent additional surgery other than tenotomy.…”
Section: Discussionmentioning
confidence: 99%
“… 1 While most patients with clubfeet can achieve satisfactory initial correction, maintaining that correction during early childhood can be challenging in some. 4 , 13 , 16 Adherence with the foot-abduction brace has been shown in multiple studies to decrease likelihood of recurrence, however, adherence with bracing does not guarantee successful long-term correction. 3 , 6 , 10 , 13 , 17 Despite adherent bracing, some feet seem almost destined to relapse, whereas poorly braced feet sometimes maintain correction over the long term.…”
Section: Methodsmentioning
confidence: 99%
“… 4 , 13 , 16 Adherence with the foot-abduction brace has been shown in multiple studies to decrease likelihood of recurrence, however, adherence with bracing does not guarantee successful long-term correction. 3 , 6 , 10 , 13 , 17 Despite adherent bracing, some feet seem almost destined to relapse, whereas poorly braced feet sometimes maintain correction over the long term. 18 The age of relapse as it relates to predictors of relapse or recurrence has not been previously studied; this is the first study assessing different patterns of recurrence of idiopathic clubfoot based on age.…”
Section: Methodsmentioning
confidence: 99%
“…In the current study, >70 % of patients had a severe deformity (grade III and IV) at birth and were therefore more resistant to well-conducted non-surgical treatment. Goldstein et al recently demonstrated that a high Dimeglio score at birth is a predictive variable for surgery [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current institution has been a pioneer in the development of the FFM and has trained physiotherapists for >40 years [ 2 , 10 ]. Despite this expertise, some severe deformities remain resistant and require further treatment [ 11 , 12 ]. As reported, a non-plantigrade and misaligned foot causes pain, sprains, and difficulties wearing shoes and results in long-term degenerative lower limb osteoarthritis in adulthood [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%